Pengaruh Media Pembelajaran Kamus Online AL-Ma’any dalam Meningkatkan Mahārah Al-Qirā’ah Pada Siswa Kelas X MAN 2 Sleman Tahun Ajaran 2017/2018 - Aidah Fitriya (Edulab : Majalah Ilmiah Laboratorium Pendidikan, 2020)
This study aims to determine how the application of Al-Ma'any online dictionary media and whether there is a difference between learning that uses Al-Ma'any online dictionary media and those who do not use Al-Ma'any online dictionary media for Mahārah of Al-Qirā’ah in class X MAN 2 Sleman. This study uses a quantitative approach while the type of research is Experimental Research. The sample in this study was 60 students, consisting of class X MIA I which was used as an experimental class with a total of 30 students and class X MIA II which was used as a control class with a total of 30 students. For data collection techniques in this study using conservation, test and documentation. Analysis of the data using T test analysis with analysis requirements Normality Test using Kolmogrof-Smirnov and homogeneity. The results of this study indicate that learning Arabic by using Al-Ma'āny online dictionary learning media can improve the Mahārah of Al-Qirā'ah in the learning of Arabic students. This is demonstrated by using SPSS 19. The output results show that in the Independent Sample Test t-test the posttest value of the experimental class students found that a significant value of 0,000 <0.05 and from the analysis of the T test the value of T counted 5.148> T table 2.045, then H0 is rejected, meaning that there is a difference in the use of Al-Ma'āny's online dictionary learning media for the learning of the Mahārah of Al-Qirā'ah Keywords: Learning Media, Al-Ma’any Dictionary. mahārah Al-Qirā’ah